Carbon Dots with Intrinsic Bioactivities for Photothermal Optical Coherence Tomography, Tumor‐Specific Therapy and Postoperative Wound Management. Issue 6 (7th January 2022) - Liu, Hao; Mo, Luoqi; Chen, Haolin; Chen, Chao; Wu, Jiayi; Tang, Zhilie; Guo, Zhouyi; Hu, Chaofan; Liu, Zhiming
Abstract: Carbon dots (CDs) are considered as promising candidates with superior biocompatibilities for multimodel cancer theranostics. However, incorporation of exogenous components, such as targeting molecules and chemo/photo therapeutic drugs, is often required to improve the therapeutic efficacy. Herein, an "all‐in‐one" CDs that exhibit intrinsic bioactivities for bioimaging, potent tumor therapy, and postoperative management is proposed. The multifunctional CDs derived from gallic acid and tyrosine (GT‐CDs) consist of a graphitized carbon core and N, O‐rich functional groups, which endow them with a high near‐infrared (NIR) photothermal conversion efficiency of 33.9% and tumor‐specific cytotoxicity, respectively. A new imaging modality, photothermal optical coherence tomography, is introduced using GT‐CDs as the contrast agent, offering the micrometer‐scale resolution 3D tissue morphology of tumor. For cancer therapy, GT‐CDs initiate the intracellular generation of reactive oxygen species in tumor cells but not normal cells, further induce the mitochondrial collapse and subsequent tumor cellular apoptosis. Combined with NIR photothermal treatment, synergistic antitumor therapy is achieved in vitro and in vivo. GT‐CDs also promote the healing process of bacteria‐contaminated skin wound, demonstrating their potential to prevent postoperative infection. The integrated theranostic strategy based on versatile GT‐CDs supplies an alternative easy‐to‐handle pattern for disease management. Abstract : "All‐in‐one" carbon dots derived from gallic acid and tyrosine (GT‐CDs) are proposed for multimodel nanotheranostics. GT‐CDs exhibit high near‐infrared photothermal conversion efficiency and tumor‐specific cytotoxicity that allow the photothermal optical coherence tomography and high‐performance synergistic tumor therapy. The intrinsic bioactivities of GT‐CDs also endow them with the potential for wound healing of bacteria‐contaminated skin.